2019
DOI: 10.1016/j.psyneuen.2019.104446
|View full text |Cite
|
Sign up to set email alerts
|

Daily perceived stress and time to pregnancy: A prospective cohort study of women trying to conceive

Abstract: Background: Prior studies among women with impaired fecundity have consistently demonstrated a positive association between daily perceived stress and the ability to conceive. However, the effects of daily stress on time to pregnancy (TTP) among women with proven fertility is not known. Materials and Methods:One hundred and forty-three women ages 18-35, in a relationship of proven fertility, who desired to conceive were included in the analysis. Daily diaries recording perceived stress (scale 0-10) were comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Association Between Neighborhood Disadvantage and Decreased Fertility poorer in vitro fertilization outcomes 18 and reduced fecundability among couples attempting spontaneous conception. 19,20 Similar results have also been found for salivary α-amylase, a biomarker of stress levels, and fecundability. 21,22 To our knowledge, no studies of disadvantaged neighborhood environment have directly examined fertility-related outcomes in the US.…”
Section: Jama Network Open | Environmental Healthsupporting
confidence: 73%
“…Association Between Neighborhood Disadvantage and Decreased Fertility poorer in vitro fertilization outcomes 18 and reduced fecundability among couples attempting spontaneous conception. 19,20 Similar results have also been found for salivary α-amylase, a biomarker of stress levels, and fecundability. 21,22 To our knowledge, no studies of disadvantaged neighborhood environment have directly examined fertility-related outcomes in the US.…”
Section: Jama Network Open | Environmental Healthsupporting
confidence: 73%
“…A potential confounding factor would be acute illness or stressful events that might reduce the events of intercourse during a cycle to zero, and also might disturb or alter cycle characteristics. Only one of the cohorts (TTP) had information noted systematically for daily stress and stressful events; in a prior analysis of that cohort, higher stress did not cause reduced fecundability, but the impact on cycle characteristics was not specifically studied ( Park et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the process of progressively experimenting with multiple methods to discover the effective method elicited self-doubt and stress for the women in our pilot study. A review of the literature revealed that (1) daily perceived stress was not adversely associated with time to pregnancy among women with proven fertility (Park et al 2019), and (2) that there is no difference in levels of stress between women using digital ovulation tests to time intercourse compared with women who were trying to conceive without any additional aids (Tiplady et al 2013). Furthermore, the use of fertility tracking provided benefits to participants, such as an increased understanding of the menstrual cycle as well as reassurance and confidence in focusing conception attempts on the correct time in the cycle (Tiplady et al 2013).…”
Section: Discussionmentioning
confidence: 99%